Heritage conservation education for tertiary level in Malaysia: Coalesce in quantity surveying programs - Zolkafli, U.K.; Kamarudin, K.; Kamal, K.S.; Rahmat, I. (2015)
Conservation practice started as the act of appreciation of heritage. It is a way to maintain, restore and repair heritage, which has been left by our ancestors, in the form of architectural remains or artifacts. Conservation of historic or heritage buildings needs an expert to do it. It is significant for students to become familiar with the general principles of conservation and with main conservation approaches towards all existing heritage buildings. Therefore the intent of this paper is to underline the need to teach undergraduates students of quantity surveying course the heritage conservation education. This aim is accomplished through the following objectives; to identify the most important of heritage conservation education to quantity surveyor students and to identify the need of heritage conservation education in quantity surveying profession. Quantitative method was selected for this study. The respondents were from the professional quantity surveyor registered with Board of Surveyors Malaysia who has experienced in building conservation project. Result showed that heritage conservation is important to the quantity surveying program because of the outstanding universal value, the nature of conservation works and the scope of quantity surveying basic services. There is a need to deliver theoretical and practical knowledge as well as skills in heritage conservation education for quantity surveying students. A combination of theoretical teaching and practical tasks in conservation education will enhance the knowledge and skills of quantity surveying students, especially in measurement, estimating, economic and construction technology for building conservation works.